New perspectives on the Great Depression: A review essay - George S. Tavlas (Duke University, Center for the History of Political Economy (CHOPE), 2016)
The Great Depression was the most devastating and destructive economic event to afflict the global economy since the beginning of the twentieth century. What, then, were the origins of the Great Depression and what have we learned about the appropriate policy responses to economic depressions from that episode? This essay reviews two recently published books on the Great Depression. Eric Rauchway's The Money Makers: How Roosevelt and Keynes Ended the Depression, Defeated Fascism, and Secured a Prosperous Peace (Basic Books, 2015) tells the story of the ways Franklin D. Roosevelt drew on the ideas of John Maynard Keynes to place monetary policy front-and-center to underpin the recovery from the Great Depression and to underwrite the blueprint of the Bretton-Woods System. Barry Eichengreen's Hall of Mirrors: The Great Depression, the Great Recession, and the Uses - and Misuses - of History (Oxford University Press, 2015) shows the way the lessons learned from analysis of the Great Depression helped shape policy makers' response to the 2007-08 financial crisis, thus helping to avoid many of the mistakes made by policy makers in the 1930s
Keywords: E52; F33; 330; Great Depression; Gold Standard; Bretton Woods System; 2008 Financial Crisis